Possible Financial Scenarios through M-Government Information Systems - LIŢAN, Daniela (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
How can technology change behaviors, by the forecast achieved on the basis of predefined scenarios even by the users of the information systems used? How could the state create a correct image in the ‘eyes’ of its citizens and keep it without significant effort? And how could each citizen conduct his/her financial ‘path’, from the early years of his/her career so that at the age of pension benefit from income (pension) based on the expectations and decisions made long ago? These are only a few questions to which I answer through this paper, customizing the solution found regarding the ‘field’ of public/private pensions by means of automations implemented in m-government information systems.
Keywords: data warehouse, information system, m-Government, mobile device, pension